AB1073 Exploration of The Difficulties Encountered by General Practitioners with Methotrexate and Tnf-Inhibitor Treatment in Common Practice. (15th July 2016) - Berthet, E.; De Rosa, M.; Vorilhon, P.; Soubrier, M.; Mathieu, S.
Abstract : Background: Rheumatic diseases are frequently occurring pathologies (approximately 1% of the population exhibits rheumatoid arthritis), causing pain, articular destruction, and functional handicaps. Early diagnosis and regular disease monitoring are required in order to avoid such complications. The therapy's objective is to attain remission, which entails optimal use of long-term treatments, such as methotrexate (MTX) or TNF-alpha inhibitors (anti-TNF alpha). These treatments are then increasingly prescribed. General practitioners (GPs) therefore must be able to manage such treatments, along with their potential side-effects. Objectives: Our study's aim was to explore the potential difficulties of GPs from the Auvergne region of France with regard to using anti-TNF alpha and MTX in their common practice. Methods: A questionnaire collecting the GPs' characteristics, difficulties in daily clinical practice, and expectations designed to ease the management of MTX and anti-TNF alpha treatments was mailed to 1, 190 GPs in our region. Results: The response rate was 24.9%, equating to 296 responses. The analysis covered 285 responses, since 11 doctors did not wish to participate. The majority of doctor respondents was men (57%) and was in group practice settings (55%). No respondents had practices situated at more than 100 km from a rheumatologist. Of the 230 GPs treating patients on MTX (81%: 230/285), 113 reported difficulties in managing therapy, such as infectious problems (30%) and the occurrence of side-effects (23%). Overall, 31% were troubled by potential drug interactions. GPs practicing for less than 10 years had more difficulties than the others (p=0.002). No significant differences were observed based on practice location, type of practice, or distance from the rheumatologist. In total, 22% of doctors surveyed (n=41) were prepared to initiate MTX therapy. Of the 189 respondents (66%) managing patients on TNF inhibitors, 127 encountered similar difficulties, yet with a higher frequency (infectious problems: 53%; side-effects: 29%, and drug interactions: 39%). No differences were observed based on GPs characteristics. Overall, 57.2% of the GPs (163/285) felt that TNF-inhibitor therapies displayed a favorable benefit/risk ratio. Amongst the respondents, 80% (228/285) desired further training. Conclusions: In our study, more than half of the GPs managing patients on MTX- or TNF-inhibitor therapy reported difficulties with the treatment. Disclosure of Interest: None declared